Electron paramagnetic resonance studies of the oxygenated and non-oxygenated LaBa2Cu3O7- delta compounds - Guskos, N.; Londos, C.A.; Lykodimos, V.; Calamiotou, M.; Koufoudakis, A.; Mitros, C.; Gamari-Seale, H.; Niarchos, D. (Journal of Physics: Condensed Matter, 1992)
The EPR spectra of polycrystalline oxygenated and non-oxygenated (large oxygen deficiency) LaBa2Cu3O7- delta compounds, obtained at various temperatures, were studied and analysed. The oxygenated samples showed a transition temperature Tc at about 50 K. The EPR spectrum of the Cu2+ ions in the orthorhombic local symmetry was observed. It was found that these spectra are essentially influenced by an oxygen deficiency and thermal treatment. In the non-oxygenated samples, at a certain stage of the annealing process an EPR spectrum was detected at low temperatures. After the final anneal, this EPR spectrum showed significant changes. Changes were also observed in the corresponding XRD spectra indicating reductions in the concentrations of the CuO and BaCuO2 impurity phases. Additionally, the EPR spectrum of divalent copper ions in the axial local symmetry in the dx2-y2 ground state was observed.